PAKAIAN MELAYU PEREMPUAN DI JAMBI KOTA SEBERANG PERIODE KESULTANAN HINGGA KEMERDEKAAN - Marlinda Mawadha, Nining; Heidi Karmela, Siti (Universitas Batanghari Jambi, 2023)
This research aims to describe the variety and meaning of the philosophy of Malay women's clothingin the Kota Jambi Seberang area and explain the changes and developments in the variety ofwomen's clothing in Kota Jambi Seberang. This research used historical method which consists offour steps, namely heuristics, criticism, interpretation and historiography. The sources used areprimary sources in the form of archives, interviews and skunder sources in the form of articles, booksand other literature. The findings showed that although in the following times there were changesand developments in Malay clothing in the Kota Jambi Seberang, it still survived and was still usedby women in daily life to certain events (official / formal) such as tengkuluk, baju kurung, and batik.In fact, there have been many new products produced from some of these Malay clothes such as batikthrough product diversification. Changes and developments are also supported due to trends,fashions, and government policies.